STRATEGI KOMUNIKASI PENYULUHAN PT. AGRO SINERGI NUSANTARA DALAM MENSOSIALISASIKAN PERJANJIAN KERJA BERSAMA TERHADAP KARYAWAN KEBUN UJUNG LAMIE - Cut Wita; Putri Maulina (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2021)
Agro sinergi nusantara in disseminating the collective labor agreement (PKB) by the directors of PT. Agro sinergi nusantara (PT. ASN) by carrying out aspects of communication planning including introduction of the company's internal and external companies, preparation of extension materials, determining methods, and selecting communication media in order to implement activities through the socialization of collective labor agreements using well-targeted communication strategies. In this study, researchers used a qualitative descriptive technique. With data collection through observation, interviews and written documentation as primary data, secondary data. Then the analytical technique used in this study is qualitative data analysis using the miles and huberman interactive analysis model.